Critical role of mammalian target of rapamycin for IL-10 dendritic cell induction by a flagellin A conjugate in preventing allergic sensitization - Schülke, Stefan; Fiedler, Anna-Helena; Junker, Ann-Christine; Flaczyk, Adam; Wolfheimer, Sonja; Wangorsch, Andrea; Heinz, Anke; Beckert, Hendrik; Nagl, Birgit; Bohle, Barbara; Vieths, Stefan; Toda, Masako; et al. (Journal of allergy and clinical immunology, 2018)
Fusion proteins incorporating the Toll-like receptor 5 ligand flagellin are currently undergoing clinical trials as vaccine candidates for many diseases. We studied the mechanisms of immune modulation by a flagellin:allergen fusion protein containing the Toll-like receptor 5 ligand flagellin A from Listeria monocytogenes and the birch pollen allergen Bet v 1 (recombinant flagellin A [rFlaA]:Betv1). BALB/c mice were vaccinated with rFlaA:Betv1 in an experimental Bet v 1 sensitization model. Myeloid dendritic cells (mDCs) were differentiated from mouse bone marrow, and PBMCs were isolated from subjects with birch pollen allergy. Cells were stimulated with equimolar amounts of rFlaA, rBet v 1, rFlaA plus rBet v 1, or the rFlaA:Betv1 conjugate and analyzed for cell activation, cytokine secretion, and metabolic state. rFlaA:Betv1 displayed strong immune-modulating properties both in vivo and in vitro, as characterized by secretion of both proinflammatory and anti-inflammatory cytokines from murine mDCs and PBMCs from patients with birch allergy. rFlaA:Betv1 suppressed TH2 responses from Bet v 1–specific CD4+ T cells and prevented allergic sensitization in a mouse allergy model. Aggregation of rFlaA:Betv1 resulted in stronger protein uptake accompanied by an increased resistance to microsomal digestion. Remarkably, rFlaA:Betv1 induced activation of mammalian target of rapamycin, which increased the metabolic activity of the stimulated mDCs. rFlaA:Betv1-mediated IL-10 secretion, but not proinflammatory cytokine secretion, was inhibited by rapamycin in mDCs. These results provide evidence that mammalian target of rapamycin is a key player involved in prevention of TH2 responses by flagellin A conjugate vaccines. [Display omitted]